Cytoplasmic Polyadenylation Element Binding Proteins CPEB1 and CPEB3 Regulate the Translation of FosB and Are Required for Maintaining Addiction-Like Behaviors Induced by Cocaine - Drisaldi, Bettina; Colnaghi, Luca; Levine, Amir; Huang, YanYou; Snyder, Anna M.; Metzger, Daniel J.; Theis, Martin; Kandel, Denise B.; Kandel, Eric R.; Fioriti, Luana (Frontiers in Cellular Neuroscience, 2020)
A recurrent and devastating feature of addiction to a drug of abuse is its persistence, which is mediated by maladaptive long-term memories of the highly pleasurable experience initially associated with consumption of the drug. We have recently found that members of the CPEB family of proteins (Cytoplasmic Polyadenylation Element-Binding Proteins) are involved in the maintenance of spatial memory. However, their possible role in the maintenance of memories that sustain addictive behavior has yet to be explored. In fact little is known about any of the mechanisms for maintaining memories for addictive behavior. To address the mechanisms whereby addictive behavior is maintained over time, we utilized a conditional transgenic mouse model expressing a dominant negative version of CPEB1 that abolishes the activity in the forebrain of two of the four CPEB isoforms (CPEB1 and CPEB3). We found that, following cocaine administration, these dominant negative (DN) CPEB mice showed a significant decrease, when compared to wild type (WT) mice, in both locomotor sensitization and conditioned place preference (CPP), two indices of addictive behavior. Supporting these behavioral results, we also found a difference between WT and DN-CPEB1-3 mice in the cocaine-induced synaptic depression in the core of the Nucleus Accumbens. Finally, we found that (1) CPEB is reduced in transgenic mice following cocaine injections, and that (2) FosB, known for its contribution to establishing the addictive phenotype, when its expression in the striatum is increased by drug administration, is a novel target of CPEBs molecules. Thus, our study highlights how CPEB1 and CPEB3 act on target mRNAs to build the neuroadaptative implicit memory responses that lead to the development of the cocaine addictive phenotypes in mammals.